2011
DOI: 10.2478/v10096-011-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Uppermost Jurassic and lowermost Cretaceous dinocyst successions of Siberia, the Subarctic Urals and Russian Platform and their interregional correlation

Abstract: Uppermost Jurassic and lowermost Cretaceous dinocyst successions calibrated against ammonite and foraminiferal zones were studied in five sections from North Siberia, the Subarctic Urals and the Russian Platform. Together with analysis of published palynological material on additional contemporaneous sections from the Russian Platform, our research provides a reliable regional correlation. The obtained biostratigraphic results are compared to palynological data from different regions of Europe, America, Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…References to additional publications on Jurassic dinocysts from Siberia can be found in , Ilyina et al (2005) and Riding (2019). Pestchevitskaya et al (2011) identified a series of Volgian to Berriasian palynostratigraphic events based on a substantial database. The data comprises material from Nordvik on the Laptev Sea coast (Nikitenko et al 2008;Nikitenko et al 2011); the Severo-Vologochanskaya-18 well at the mouth of the Yenisei River and the Zapadno-Purpeiskaya-710 well in northwestern Siberia (Beisel et al 2002); the River Yatriya in the Subarctic Urals Nikitenko 1998, 1999); and Kashpir located in the middle reaches of the River Volga Harding et al 2011).…”
Section: Nanno-ceratopsis Gracilismentioning
confidence: 99%
See 2 more Smart Citations
“…References to additional publications on Jurassic dinocysts from Siberia can be found in , Ilyina et al (2005) and Riding (2019). Pestchevitskaya et al (2011) identified a series of Volgian to Berriasian palynostratigraphic events based on a substantial database. The data comprises material from Nordvik on the Laptev Sea coast (Nikitenko et al 2008;Nikitenko et al 2011); the Severo-Vologochanskaya-18 well at the mouth of the Yenisei River and the Zapadno-Purpeiskaya-710 well in northwestern Siberia (Beisel et al 2002); the River Yatriya in the Subarctic Urals Nikitenko 1998, 1999); and Kashpir located in the middle reaches of the River Volga Harding et al 2011).…”
Section: Nanno-ceratopsis Gracilismentioning
confidence: 99%
“…The data comprises material from Nordvik on the Laptev Sea coast (Nikitenko et al 2008;Nikitenko et al 2011); the Severo-Vologochanskaya-18 well at the mouth of the Yenisei River and the Zapadno-Purpeiskaya-710 well in northwestern Siberia (Beisel et al 2002); the River Yatriya in the Subarctic Urals Nikitenko 1998, 1999); and Kashpir located in the middle reaches of the River Volga Harding et al 2011). Of particular relevance herein are the data from the several outcrops on the Nordvik Peninsula (Nikitenko et al 2008;Nikitenko et al 2011;Pestchevitskaya et al 2011). Pestchevitskaya et al (2011) compared their results to existing palynological data from America, Antarctica, Australia and Europe using first and last appearances of selected key species and evolutionary trends of dinocyst floras.…”
Section: Nanno-ceratopsis Gracilismentioning
confidence: 99%
See 1 more Smart Citation
“…Nøhr-Hansen et al 2019), the Barents Sea (Århus et al 1990;Smelror et al 1998;Smelror & Dypvik, 2005;Smelror & Dypvik, 2006;Kairanov et al 2018), Arctic Norway (Løfaldi & Thusu, 1976;Bjaerke, 1978;Thusu, 1978;Århus et al 1986, 1990Århus, 1991;Grøsfjeld, 1991;Hurum et al 2016b;Smelror & Larssen, 2016;Smelror et al 2018;Hammer et al 2018;Rakociński et al 2018;Grundvåg et al 2019) and Arctic Russia (Smelror, 1986;Lebedeva & Nikitenko, 1999;Riding et al 1999;Pestchevitskaya, 2007;Nikitenko et al 2008;Pestchevitskaya et al 2011). Some early Canadian studies provided dinocyst zonations (e.g.…”
Section: Previous Studies Of Lower Cretaceous Boreal Dinocyst Assemblmentioning
confidence: 99%
“…Более частые находки ребристых и бугорчатых спор схизейных папоротников предполагают более высокий стратиграфический интервал, возможно соответствующий верхневолжскому подъярусу -нижней части бореального берриаса. На глубине 3491,05 м определены диноцисты Apteodinium maculatum Eisenack et Cookson, наиболее древние находки которых отмечаются на севере Сибири и на Русской платформе в верхах верхневолжского подъяруса -низах бореального берриаса [Pestchevitskaya et al, 2011].…”
Section: биостратиграфияunclassified